(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2021)
The Islamic Bank of Al-Nahrain offers a formula for financing the purchase of real estate through a deferred sale contract, through Murabaha to the order to buy, and the payment of the price is in the form of instalments that include (the purchase price of the profit and the mutual agreement on the real estate). This research aims to show the reflection of real estate murabaha on the bank’s investments, by measuring the effect of real estate murabaha on the profits achieved by the Islamic Bank of Al-Nahrain Bank. The growth of ’real estate murabaha’ realized from the ’amounts granted by Bank X, in addition to analyzing the financial ratios of profitability indicators, including (return on deposits Y2) and for the years (2016 - 2020) and semi-annually for each year. Murabaha of real estate during the year (2018) due to the change of some of the regulations related to Murabaha of real estate, but the bank was able to put in place a successful strategic plan to increase the return on Murabaha of real estate in the year (2019). Including the Corona pandemic.